Update and overview on assisted reproductive technologies (ARTs) in Brazil - Sartori, R.; Prata, A. B.; Figueiredo, A. C.S.; Sanches, B. V.; Pontes, G. C.S.; Viana, J. H.M.; Pontes, J. H.; Vasconcelos, J. L.M. [UNESP]; Pereira, M. H.C. [UNESP]; Dode, M. A.N.; Monteiro, P. L.J.; Baruselli, P. S. (Colegio Brasileiro de Reproducao Animal - CBRA, 2016)
The impressive increase in the use of assisted reproductive technologies (ARTs), especially in cattle, during the last few years in Brazil is well known worldwide. In 2015, there were over 13.7 million artificial inseminations (AI), of which, about 77% were carried out using fixed-time AI (FTAI). This technology has helped to substantially improve reproductive efficiency in beef and dairy cattle. In relation to embryo transfer, production of in vivo derived (IVD) embryos remained relatively stable, with average production of 30-40,000 embryos per year, whereas in vitro production (IVP) of embryos had a substantial increase, from about 12,500 IVP embryos in 2000 to more than 300,000 IVP embryos after 2010. The increasing availability and use of sex-sorted sperm was one of the factors responsible for a recent shift from the predominance of IVP embryos from beef breeds to dairy breeds in Brazil. Moreover, there was also an increase from 13% in 2014 to 29% in 2015 in the percentage of vitrified/frozen embryos. Moreover, the successful use of protocols for fixed-time ET (FTET) due to their high efficiency and ease of implementation, has facilitated the dissemination of ET programs all over Brazil. However, there is room for improvement, since there are several reports of high pregnancy loss and high peripartum loss, when IVP embryos are used. The production of healthy cattle by somatic cell nuclear transfer has also increased in the last few years in Brazil, but despite substantial progress in reducing postnatal losses, no drastic increase in cloning efficiency up to parturition has occurred.
Keywords: Artificial insemination; Bovine; Embryo; In vitro production; Superovulation